Private Property Rights and the Environment Our Responsibilities to Global Natural Resources - Hiller Marguerat, Shelly (Palgrave Studies in Environmental Policy and Regulation,, 2019)
This book explores the current notion and definition of property, and its interpretation and implementation in relation to the environment. The author examines two primary problems: the degradation of land, natural resources and animal abuse; and the increasing erosion of private property rights from property owners by the arbitrary interference of state governments. Examining texts from antiquity to contemporary legislation, it portrays the historical development of the understanding of "nature" as "property" and discusses our obligations towards the environment. Drawing on the most influential political-philosophical texts from all periods of property rights history, the author analyzes modern national and international legislation and case law to offer legally-grounded evidence and explanations. This book advocates the incorporation of a formula that guarantees the protection of property rights into the legal system, and imposes clear and effective responsibility on property owners to limit the use of natural resources and the abuse of animals. This book will appeal to practitioners, researchers and students with an interest in environmental and private property law.